Dynamic Modeling and Controller Design of DSTATCOM in a Microgrid Based on Combination of Fuzzy Set and Galaxy-based Search Algorithm. Issue 1 (1st January 2018) - Tolabi, Hajar Bagheri; Shakarami, Mahmoud Reza; Ara, Afshin Lashkar; Hosseini, Rahil
ABSTRACT: This article has been retracted